1973
DOI: 10.2134/agronj1973.00021962006500020037x
|View full text |Cite
|
Sign up to set email alerts
|

“Reductants” Released by Roots of Fe‐Deficient Soybeans1

Abstract: Iron‐stressed (deficient) ‘Hawkeye’ (HA) releases more “reductant” into nutrient solutions than PI‐54619‐5‐1 (PI) soybean [Glycine max (L.) Merrill] roots. These two plants differ in their response to Fe stress and their susceptibility to Fe chlorosis. The objective of this study was to characterize the “reductant” and to determine its role in the uptake of Fe by HA and PI soybeans. Reducing capacity of the ‘reductant’ was determined by its ability to reduce ferric to ferrous iron. Fe2+ was measured using 2,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 7 publications
1
31
0
1
Order By: Relevance
“…In sunflower under conditions of iron deficiency, there was an accumulation of o-diphenolics (14), as well as a release of reducing substances into the nutrient solution (10). A similar release was reported for soybeans (2,3) and tomatoes (12). In tomato, caffeic acid and three other p-coumaric acid derivates were released into the nutrient solution (12).…”
Section: Romheld and Marschnersupporting
confidence: 77%
See 1 more Smart Citation
“…In sunflower under conditions of iron deficiency, there was an accumulation of o-diphenolics (14), as well as a release of reducing substances into the nutrient solution (10). A similar release was reported for soybeans (2,3) and tomatoes (12). In tomato, caffeic acid and three other p-coumaric acid derivates were released into the nutrient solution (12).…”
Section: Romheld and Marschnersupporting
confidence: 77%
“…These changes include the formation of rhizodermal transfer cells (7), the accumulation of reducing substances in the rhizodermis, and an enhanced proton efflux: they facilitate iron uptake (2,14).…”
mentioning
confidence: 99%
“…In support of this, it was found that when plants were grown in nutrient solutions which had pH values below 4.0, compounds accumulated in the nutrient solutions which were capable of reducing inorganic Fe"' to Fe" over a 20-to 24-h period. The release of reductants in the nutrient solutions was greater with Fe-deficient than Fe-adequate plants (2,17,20,23). An investigation with HPLC suggested that the major secreted reductants were caffeic acid and p-coumaric acid (20).…”
mentioning
confidence: 97%
“…4 Excretion of organic compounds, mainly phenolics or flavins, have been associated with the Fe deficiency response since the early seventies, 5,6 but were later considered to be of minor importance and, with some notable exceptions (e.g., the massive production of riboflavin and riboflavin derivatives by some species), 7,8 were largely neglected in studies related to iron acquisition processes in model species such as Arabidopsis. Nevertheless, the frequent observation of this phenomenon led to speculations on the function of these compounds in Fe acquisition, comprising effects on the microbiome in the rhizosphere, a function (for flavins) in electron transport during the reduction of Fe(III), chelation of Fe, and chemical reduction of Fe(III).…”
mentioning
confidence: 99%